Making omnichannel an augmented reality: the current and future state of the art. Issue 4 (8th October 2018) - Hilken, Tim; Heller, Jonas; Chylinski, Mathew; Keeling, Debbie Isobel; Mahr, Dominik; de Ruyter, Ko
Abstract : Purpose: This paper aims to explore the current and future roles of augmented reality (AR) as an enabler of omnichannel experiences across the customer journey. To advance the conceptual understanding and managerial exploitation of AR, the paper aims to synthesise current research, illustrating how a variety of current applications merge online and offline experiences, and provides a future research agenda to help advance the state of the art in AR. Design/methodology/approach: Drawing on situated cognition theorising as a guiding framework, the paper reviews previously published research and currently deployed applications to provide a roadmap for future research efforts on AR-enabled omnichannel experiences across the customer journey. Findings: AR offers myriad opportunities to provide customers with a seamless omnichannel journey, smoothing current obstacles, through a unique combination of embedded, embodied and extended customer experiences. These three principles constitute the overarching value drivers of AR and offer coherent, theory-driven organising principles for managers and researchers alike. Originality/value: Current research has yet to provide a relevant, conceptually robust understanding of AR-enabled customer experiences. In light of the rapid development and widespread deployment of the technology, this paper provides an urgently needed framework for guiding the development of AR in an omnichannel context.